Cerro del Pueblo Fm (Difunta Group, Upper Cretaceous), Parras Basin, southern Coahuila, Mexico: reference sections, age, and correlation - David A. Eberth; Carlos R. Delgado-de Jesús; John F. Lerbekmo; Donald B. Brinkman; Rubén A. Rodríguez-de la Rosa; Scott D. Sampson (Revista Mexicana de Ciencias Geológicas)
Principal and supplementary reference sections provide data that clarify the stratigraphic relationships and depositional history of the Cerro del Pueblo Formation (CdP) – an important unit in Late Cretaceous paleobiogeographic studies in northeastern Mexico and the Western Interior of North America. At Saltillo, the CdP is 162 m thick, much thinner than previously reported. To the west, however, the CdP thickens to 449 m at Rincón Colorado (35 km west of Saltillo) and 540 m at Porvenir de Jalpa (70 km west of Saltillo). A substantial stratigraphic interval of interbedded grey-green and red beds is present above the CdP throughout the field area; for consistency, it is assigned to the overlying Cerro Huerta Formation (CH).